PROBLEMATIKA PEMAHAMAN QIRĀ’ĀT DI KALANGAN GENERASI KONTEMPORER: STUDI ANALISIS DALAM PERSPEKTIF ULUMUL QUR’AN - Ikhlash Hidayatullah; Asyhar Mubarak; Ali Akbar; Edi Hermanto; Fatmah Taufik Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The science of qirā’āt constitutes a significant discipline within the study of Ulum al-Qur’an, focusing on the variant modes of Qur’anic recitation that have been authentically transmitted (mutawātir) from the Prophet Muhammad (peace be upon him). The existence of qirā’āt demonstrates that the preservation of the Qur’an encompasses not only its written form but also its oral dimension, which has been meticulously maintained through continuous chains of transmission (sanad). Within the classical Islamic scholarly tradition, qirā’āt is understood as part of the divine facilitation (taysīr) granted to the Muslim community, as reflected in the prophetic tradition concerning the revelation of the Qur’an in seven modes (sab‘atu ahruf) (al-Bukhari and Muslim). However, in the contemporary context, the understanding of qirā’āt among Muslim generations faces a range of complex challenges. Current trends indicate a narrowing of comprehension, where the majority of Muslims are familiar only with a single transmission, namely the narration of Ḥafṣ ‘an ‘Āṣim, without adequate awareness of other equally valid canonical recitations (az-Zarqānī, Manāhil al-‘Irfān). This condition is further exacerbated by the influence of digital media, which often simplifies Qur’anic learning, as well as the insufficient integration of qirā’āt studies within Islamic educational systems. The findings reveal that the primary issues lie in the low level of qirā’āt literacy, the dominance of a single recitational tradition in educational practice, and the lack of methodological understanding regarding the principles and validity of qirā’āt. Furthermore, technological developments, when not accompanied by proper scholarly guidance, contribute to the persistence of misconceptions about the diversity of Qur’anic recitation. Therefore, revitalization efforts are necessary through strengthening educational curricula, developing adaptive teaching methods, and utilizing technology responsibly to enable contemporary generations to comprehend qirā’āt comprehensively as an integral aspect of the Qur’an’s authenticity.